Assessment of tuberculosis prevalence in newly diagnosed human immunodeficiency virus-infected adults attending care and treatment center in Gujarat, India - Dixitkumar Jayantibhai Kapadiya; Paresh V Dave; Bhavin Vadera; Pranav Govindbhai Patel; Sudhir Chawla; Deepak Saxena (Wolters Kluwer Medknow Publications, 2018)
Background: Tuberculosis (TB) is first opportunistic infection and leading cause of death among human immunodeficiency virus (HIV)/AIDS. Certainly, the prevalence of TB is expected to differ between general population and HIV-infected persons. This study was conducted to determine the prevalence of TB among newly diagnosed HIV-infected adults attending antiretroviral therapy (ART) center in the state of Gujarat, India. Materials and Methods: Cross-sectional study was carried out among newly diagnosed HIV-infected persons attending ART center from July 2012 to September 2012. Screening of TB symptoms and chest X-ray was done for those who consented. Sputum samples were collected for microscopy with Ziehl-Neelsen method for all presumptive TB cases and those diagnosed as pulmonary TB, culture, and drug susceptibility test was done. Blood samples were collected for CD4+ T-cells count and hemoglobin. Results: Out of 2021 eligible HIV-infected persons, 63.5% were males and 68.2% were in the age group of 26-45 years. The prevalence of TB was 17.8%. Among 360 patients with TB, 102 (28%) had smear positive TB, 86 (24%) had smear-negative TB, and 172 (48%) were diagnosed as extrapulmonary TB. Two hundred and thirty-eight (27%) TB patients with CD4+ T-Cell count below 200 compared to 122 (11%) patients above 200. Conclusion: A high prevalence of TB was found among newly diagnosed HIV-infected adults attending ART center for care and treatment. The prevalence of pulmonary and extrapulmonary TB was almost equal. Chances of TB disease were more with depletion of CD4 counts. The study highlights urgent need of intensive case finding as well as periodic screening of newly diagnosed HIV-infected individuals.